Symposium: Australia-US Economic Relations and the Regional Balance of PowerAustralia-US Economic Relations following the 2005 Free Trade Agreement - Kelton, Maryanne (Australian journal of political science, 2013)
The Australia-United States Free Trade Agreement (AUSFTA) came into force on 1 January 2005. Australia's exports to the US have since stagnated, while imports into and US investments in Australia have surged. This article analyses Australia-US economic relations with a focus on trade and investment flows. In addition, it examines the capital raising by US investment banks for these projects. The analysis traces the effects on the relationship of the Global Financial Crisis, the resources boom in Australia and the rise of the Australian dollar. 澳美自由贸易协定2005年元旦起生效。自那以来，澳大利亚对美出口止步不前，而来自美国的进口和投资却一路上扬。本文考察了澳美经济关系，重点分析了贸易和投资流。此外作者还研究了美国投资银行为那些项目的融资。以往分析研究探索了全球金融危机、澳大利亚起源开发热以及澳大利亚元升值三者之间关系所受的影响。